PENGARUH PROFESIONALIME AUDITOR DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGEMENT (KAP Provinsi Banten) - Dirvi Surya Abbas; Basuki Basuki (Universitas Muhammadiyah Tangerang, 2019)
This study aims to obtain empirical evidence regarding the influence of Professionalism and Auditor's Experience on Audit Judgment. This study uses a Convience sampling technique and obtained a sample of 79 auditors at the Public Accounting Firm in Banten Province. Testing the hypothesis in this study was carried out by using multiple linear regression test analysis. The results of the first research hypothesis indicate that in the model there is a significant effect of auditor professionalism on audit judgment, with the results of tcount> ttable (4,208> 1,991) which illustrates that the higher the level of professionalism an auditor has, judgment judgments in making a decision in the formation of an idea, opinion or estimate of an object, event, status, or other type of event by prioritizing its responsibilities as a profession and managing the code of ethics in accordance with SPAP which becomes the auditor's reference in attitude. then the results of the second research hypothesis indicate that the Auditor's Experience has no effect on Audit Judgment with the results of tcount> ttable (-0.239 <1.991), the auditor's experience does not see the auditor's flight hours in auditing, the number of audit assignments he has handled will increase the auditor's ability to detect errors in auditing and making an awareness of mistakes that have occurred during the time of being an auditor so that this becomes an obstacle for the auditor to conduct a judgment audit. Keywords : Profesionalisme Auditor, Pengalaman Auditor, dan Audit Judgement.